2011
DOI: 10.1007/s10336-011-0660-y
|View full text |Cite
|
Sign up to set email alerts
|

Social and habitat correlates of immigrant recruitment of yearling female Mallards to breeding locations

Abstract: Conspecific avoidance and attraction hypotheses have been proposed to explain patterns of animal spacing behavior and have been frequently used to explain habitat selection by dispersers. In birds, tests of these hypotheses have been limited to fine spatial scales and have not considered dispersal distance. We used discriminant function analysis (DF) of feather d 34 S, dD, d 15 N and d 13 C values to identify yearling female Mallards (Anas platyrhynchos) that dispersed long distances ([400 km relative latitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…ConspeciWc attraction has long been recognized as an important factor in avian habitat selection (Hilden 1965), and recent observational and experimental work has shown that conspeciWc attraction can convey useful information about habitat quality and breeding success Doligez et al 2004;Ward and Schlossberg 2004). Few waterfowl studies have explicitly studied conspeciWc attraction, but each has found that conspeciWc attraction can be a more important cue than habitat in nest site selection (Pöysä et al 1998;Coulton et al 2011).…”
Section: Dispersion Of Nests Within a Weldmentioning
confidence: 99%
“…ConspeciWc attraction has long been recognized as an important factor in avian habitat selection (Hilden 1965), and recent observational and experimental work has shown that conspeciWc attraction can convey useful information about habitat quality and breeding success Doligez et al 2004;Ward and Schlossberg 2004). Few waterfowl studies have explicitly studied conspeciWc attraction, but each has found that conspeciWc attraction can be a more important cue than habitat in nest site selection (Pöysä et al 1998;Coulton et al 2011).…”
Section: Dispersion Of Nests Within a Weldmentioning
confidence: 99%
“…Relationships between anthropogenic disturbances and breeding success may be different than those observed for breeding pair settling if different ecological processes influence female survival, nest success, and/or duckling survival. Furthermore, immigration of pairs from other regions could mask effects of reduced local breeding success (Coulton et al 2011), creating population sinks. Thus, a more thorough assessment of anthropogenic disturbances as foci for conservation action requires examination of both pair settling and their breeding success.…”
Section: Discussionmentioning
confidence: 99%
“…Our results have management and conservation implications and offer some insight on the divergent trajectories that appear to characterize nest site selection studies by gamebird vs. non-gamebird bird ecologists. A large number of studies have now recognized the importance of both social and personal information use in nest site selection by birds (Ahlering et al 2010;Ahlering and Faaborg 2006;Betts et al 2008;Campobello and Sealy 2011;Chalfoun and Schmidt 2012;Coulton et al 2011;Nocera and Betts 2010;Szymkowiak 2013;Ward et al 2010). However, studies of waterfowl have focused more on habitat characteristics affecting nesting behaviors, while studies of passerines tend to focus more on the importance of social information (see also Eichholz and Elmberg 2014;O'Neil et al 2014).…”
Section: Discussionmentioning
confidence: 99%